Rubber tire retaining wall - Chew, Wai Hoong. (Universiti Malaysia Sarawak (UNIMAS), 2001)
More landslides occur in Malaysia nowadays. This phenomenon frequently occurs at hillsides when the structure of the soil is unstable. Landslide not only damages the beauty of Mother Nature, it also threatens the life of those who stay nearby.